Design and simulation of PZT Piezoelectric Microphone - Muhammad Aiman Ab. Mahat (Universiti Malaysia Perlis, 2008)
Microphone is one of the most challenging and developing areas and markets in the field of micro sensor technology. Piezoelectric is one of sensing and actuation methods in Micro Electro Mechanical System or MEMS. This report present of two phenomenon of piezoelectric – direct and inverse effect of piezoelectricity. PZT or lead frame zirconate titanate is a material of piezoelectric that can be used for both sensing and actuation purpose. An initial research found that a microphone is an application of the piezoelectric effect. The project also proved that, that piezoelectric effect included both mechanical and electrical element.